A CDR-based approach to generate covalent inhibitory antibody for human rhinovirus protease. (15th July 2021) - Cheng, Yaping; Wu, Jingyuan; Han, Ying; Xu, Jingyao; Da, Yifan; Zhao, Qian; Guo, Guoying; Zhou, Yani; Chen, Yimin; Liu, Jinghong; Chen, Huayao; Jiang, Xianxing; et al.
Graphical abstract: Abstract: Covalent target modulation with small molecules has been emerging as a promising strategy for drug discovery. However, covalent inhibitory antibody remains unexplored due to the lack of efficient strategies to engineer antibody with desired bioactivity. Herein, we developed an intracellular selection method to generate covalent inhibitory antibody against human rhinovirus 14 (HRV14) 3C protease through unnatural amino acid mutagenesis along the heavy chain complementarity-determining region 3 (CDR-H3). A library of antibody mutants was thus constructed and screened in vivo through co-expression with the target protease. Using this screening strategy, six covalent antibodies with proximity-enabled bioactivity were identified, which were shown to covalently target HRV14-3C protease with high inhibitory potency and exquisite selectivity. Compared to structure-based rational design, this library-based screening method provides a simple and efficient way for the discovery and engineering of covalent antibody for enzyme inhibition.